KETAHANAN PAKAN TERNAK INDONESIA - Endah Subekti (MEDIAGRO, 2009)
Meat, egg, and milk are represent yielded product by livestock. There are very important as source of required animal protein to human life. These days, resident of Indonesia amounting to not less than 250 million people. There are of course require big enough livestock production also utilize to fullfiil requirement of society to requirement of the animal protein. In effort  ranch, feed have important role in determining growth rate as well as determining amount and quality from yielded product by livestock. The feed also represen the biggest production cost factor in effort ranch that is around 60-70% from production total cost. Considering is important of the feed, hence needing the existence of serious attention to availibility of feed, so that earning available a speel of, so that the effort ranch of people can continue to go forward and expand to utilize can fullfill requirement of society to animal protein. Therefore this writing aim to know efforts which can be conducted to realize feed security in Indonesia utilize to guarantee the continuity of the effort rench of people, so that we can fullfill requirement of society animal protein self sufficiency. Key words : Feed, security, Indonesia